The role of neuroimmune and inflammation in pediatric uremia-induced neuropathy - Zhu, Linfeng; Tong, Guoqin; Yang, Fan; Zhao, Yijun; Chen, Guangjie (Frontiers in Immunology, 2022)
Uremic neuropathy in children encompasses a wide range of central nervous system (CNS), peripheral nervous system (PNS), autonomic nervous system (ANS), and psychological abnormalities, which is associated with progressive renal dysfunction. Clinically, the diagnosis of uremic neuropathy in children is often made retrospectively when symptoms improve after dialysis or transplantation, due to there is no defining signs or laboratory and imaging findings. These neurological disorders consequently result in increased morbidity and mortality among children population, making uremia an urgent public health problem worldwide. In this review, we discuss the epidemiology, potential mechanisms, possible treatments, and the shortcomings of current research of uremic neuropathy in children. Mechanistically, the uremic neuropathy may be caused by retention of uremic solutes, increased oxidative stress, neurotransmitter imbalance, and disturbance of the blood-brain barrier (BBB). Neuroimmune, including the change of inflammatory factors and immune cells, may also play a crucial role in the progression of uremic neuropathy. Different from the invasive treatment of dialysis and kidney transplantation, intervention in neuroimmune and targeted anti-inflammatory therapy may provide a new insight for the treatment of uremia.